Cardiovascular activity of Labdane Diterpenes from andrographis paniculata in isolated rat hearts - Awang, Khalijah; Abdullah, N.H.; Hadi, A.H.; Su Fong, Y. (Hindawi Publishing Corporation, 2012)
The dichloromethane (DCM) extract of Andrographis paniculata Nees was tested for cardiovascular activity. The extract significantly reduced coronary perfusion pressure by up to 24.5 ± 3.0 mm Hg at a 3 mg dose and also reduced heart rate by up to 49.5 ± 11.4 beats/minute at this dose. Five labdane diterpenes, 14-deoxy-12-hydroxyandrographolide (1), 14-deoxy-11,12-didehydroandrographolide (2), 14-deoxyandrographolide (3), andrographolide (4), and neoandrographolide (5), were isolated from the aerial parts of this medicinal plant. Bioassay-guided studies using animal model showed that compounds, (2) and (3) were responsible for the coronary vasodilatation. This study also showed that andrographolide (4), the major labdane diterpene in this plant, has minimal effects on the heart.